Creative language: aphorisms, parables and fables of spirituality in modern literature - Altabaa, Homam; Hamawiya, Adham (2019)
Kahlil Gibran is arguably one of the most significant poets and novelists of Arabic literature and a leading figure in popular American poetry in the twentieth century. His works, beginning with “Music” in 1905 and ending with “The Wanderer” in 1932, convey profound spiritual and idealist messages. A majority of his works seeks a social and spiritual utopia, although some works seem to be a strong condemnation of organized religion and the church. This paper seeks to explore the spiritual messages expressed in the English works of Gibran through the media of aphorisms, parables and fables. The use of these genres has been historically well studied in the religious and literary contexts, as is the case, for instance, with the parables of the New Testament and Aesop’s Fables. However, the use of aphorisms, parables and fables in a modern spiritual context, especially in the case of Gibran, has not been extensively examined. The aim of this paper is to gain a better appreciation of this literary giant’s creative use of language that ensured his universal success and enduring fame across cultures.